Towards a Communicative Test of Reading and Language Use for Classical Greek. Issue 44 (2021) - Poupounaki-Lappa, Polyxeni; Peristeri, Tzortzina; Coniam, David
Abstract: This paper describes the development of a communicative test of Reading and Language Use for Classical Greek, aimed at students at CEFR (Common European Framework of Reference for Languages) levels A1 and A2. A discussion is first provided of traditional pedagogical approaches which have for many decades dominated the teaching of classical languages, followed by suggestions why these may be supplanted with more modern communicative approaches. Focus then moves to assessment, where, it is suggested, methods are equally rooted in traditional, form-focused methods. If teaching is to become more communicative, it is argued, so should assessment. Against this backdrop, the development of a test of Reading and Language Use for students of Classical Greek at CEFR levels A1 and A2 is described.